1978
DOI: 10.2466/pr0.1978.43.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Academic Achievement in Three Educational Levels

Abstract: This study was undertaken to examine the relationship between “personality fitness” and academic achievement. 175 subjects from three educational levels, university, vocational technical institute, and high school, were administered the Eysenck Personality Questionnaire, the Raven's Advanced Progressive Matrices, and an Information Questionnaire. The personality dimension of introversion had the highest correlation with academic performance for the university sample, especially for the students in the “hard sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 11 publications
1
25
0
2
Order By: Relevance
“…As Psychoticism relates to insensitivity, solitariness and an uncaring attitude, and as such a trait is more likely to be negatively associated with educational settings, this result is unsurprising. Conscientiousness (a FFM trait) is positively related to achievement (not surprisingly) (Goh & Moore, 1987;Busato, et al 2000;Blickle, 1996& Costa & McCrae, 1992. Openness/Intuition (FFM and MBTI traits) have been positively associated with academic performance.…”
Section: Multi-trait Models and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…As Psychoticism relates to insensitivity, solitariness and an uncaring attitude, and as such a trait is more likely to be negatively associated with educational settings, this result is unsurprising. Conscientiousness (a FFM trait) is positively related to achievement (not surprisingly) (Goh & Moore, 1987;Busato, et al 2000;Blickle, 1996& Costa & McCrae, 1992. Openness/Intuition (FFM and MBTI traits) have been positively associated with academic performance.…”
Section: Multi-trait Models and Learningmentioning
confidence: 99%
“…Eysenck & Cookson, (1969) found that the correlation between Extroversion and achievement changed from a positive to a negative correlation around the ages of 13-14. It is now generally accepted that Introverts (EPQ, FFM and MBTI traits) have an advantage in learning and are more likely to have better study habits (Goh & Moore, 1987;Sanchez-Marin, et al 2001), although contradictions remain. In reviewing nine studies connected with second language learning, Kiany (1998) found that two detected a positive relationship with Extroversion and L2 success, three found a positive relationship with Introversion and L2 success, and three found no link.…”
Section: Multi-trait Models and Learningmentioning
confidence: 99%
“…Other studies found that more stable students have also higher academic performance and achievement in post secondary and university education (Cattell and Kline, 1977;Goh and Moore, 1978;Sanchez-Marin, RejanoInfante and Rodriguez-Troyano, 2001;Lathey, 1991). The negative relationship between academic achievement (particularly examinations) and neuroticism that have been found in several previous studies and meta-analyses has been explained in terms of high stress and anxiety of neurotic students under test or examination conditions (Zeinder and Matthews, 2000).…”
Section: (Literature Review)mentioning
confidence: 99%
“…Nevertheless, these factors explained only 20% of the variance in academic achievement. Results obtained with the Eysenck Personality Questionnaire (Eysenck & Eysenck, 1975) have shown that psychoticism, negatively and independently of age, is the dimension which is most consistently related to academic achievement (Goh & Moore, 1978;Aluja & Torrubia, 1998).…”
Section: Introductionmentioning
confidence: 99%